Pengaruh Sistem Senioritas Atau Nenkojoretsu Terhadap Perkembangan Karir Karyawan Lokal Berpendidikan S1 Di Perusahaan Jepang Di Indonesia - Marion, Elisa Carolina; Handayani, Ratna; Koda, Natsumi (Bina Nusantara University, 2012)
Seniority system in Japan known as nenkojoretsu is a culture that influences the management system of Japanese companies operating in Indonesia, including the promotion system for career development of the employees. This study aims to find out more about the seniority system which runs on Japanese companies in Indonesia. This research can also broaden the knowledge of Japanese language students who seek a career in Japan corporates. We use a questionnaire as data collection technique. The result is then analyzed using descriptive analysis. This study finds that there is a position change for respondents who occupy staf positions for more than fifteen years of work since entering work. Though, some of them have not changed position yet.